In vivo Assessment of Localised Corneal Biomechanical Deterioration With Keratoconus Progression - Lopes, Bernardo T.; Padmanabhan, Prema; Eliasy, Ashkan; Zhang, Haixia; Abass, Ahmed; Elsheikh, Ahmed (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To evaluate the regional corneal biomechanical deterioration with keratoconus (KC) progression as measured by the Stress-Strain Index (SSI) maps. Methods: The preoperative examinations of 29 progressive KC cases that were submitted to corneal cross-linking (CXL) were evaluated. The examinations included the tomography and the SSI measured by the Pentacam HR and the Corvis ST (Oculus, Wetzlar, Germany), respectively. The results were recorded twice, the latter of which was at the last visit before the CXL procedure. The patient-specific SSI maps were built, using data at each examination, based on finite element modelling and employing inverse analysis to represent the regional variation of biomechanical stiffness across the cornea. Results: All cases presented significant shape progression (above the 95% CI of repeatability) in anterior and posterior curvatures and minimum thickness. The overall corneal stiffness as measured by the SSI within the central 8mm-diameter area underwent slight but significant reductions from the first to the last examination (-0.02 ± 0.02, range: -0.09 to 0, p < 0.001). In all 29 cases, the reduction in stiffness was localised and concentred in the area inside the keratoconus cone. The SSI values inside the cone were significantly lower in the last examination (by 0.15 ± 0.09, range: -0.42 to -0.01, p < 0.001), while the SSI outside the cone presented minimal, non-significant variations (0 ± 0.01, range: -0.04 to 0.01, p = 0.999). Conclusions: It has been observed through the SSI maps that the regional deterioration in stiffness was concerted inside the area of pathology, while only mild non-significant alterations were observed outside the area of pathology.